Optimal portfolio selection decision making before and after Malaysia general elections using game theory approach - Muhammad Akram Ramadhan Ibrahim (Kulliyyah of Science, International Islamic University Malaysia, 2020)
The change of the Malaysia government during its 14th general election (GE14) has motivated this research to study the general elections impact on the stock market performance. The aim is to determine the impact of Malaysia 13th and 14th general elections towards the chosen stocks in FBMKLCI by using the cooperative game theory approach. The players (sectors) are divided into three groups where each player will have several different strategies (stocks) for the game. The sectors involve are financial services, consumer products and services, and telecommunications and media. The stocks in the financial services sector are AMMB Holding Bhd, CIMB Group Holdings Bhd, Hong Leong Bank Bhd, Hong Leong Financial Bhd, Malayan Banking Bhd, Public Bank Bhd and RHB Capital Bhd. The stocks in the consumer products and services sector are PPB Group Bhd, Genting Bhd, Genting Malaysia Bhd and Petronas Dagangan Bhd. The stocks in the telecommunications and media sector are Axiata Group Bhd, Digi.Com Bhd and Maxis Bhd. The payoff for each sector and its coalition are calculated by averaging the stocks' returns. The value of the game for each sector is obtained by using Nash equilibrium solution concept. Then the values of the game are considered as characteristic functions to obtain the Shapley value solution concepts in cooperative game theory framework. The Shapley value percentages are calculated by normalizing its value with the grand coalition value. The Shapley value percentages for GE13 and GE14 are compared to indicate the impact of GE14 on investment. The aim continues to construct the optimal portfolio selection based on the Shapley value percentages for GE14 only and measure its performance by using Sharpe ratio for one year. The result shows that the Shapley optimal portfolio dominates the market portfolio and the naive diversification portfolio in the period from February 2018 until November 2018. This shows that Shapley optimal portfolio performs better during GE14.